Changes over time in quality of life of school-aged children born extremely preterm: 1991–2005. Issue 4 (17th February 2021) - Peart, Stacey; Cheong, Jeanie Ling Yoong; Roberts, Gehan; Davis, Noni; Anderson, Peter J; Doyle, Lex W
Abstract : Objective: To compare health-related quality of life (HRQOL) at 8 years in children born extremely preterm (EP) with contemporaneous term-born controls over three epochs: 1991–92, 1997 and 2005. Design: Prospective recruitment of geographic cohorts across three distinct eras. Utilities were calculated from the parent-completed Health Utilities Index (HUI), version 2 (1991–92 and 1997 cohorts) and version 3 (2005 cohort). Differences in utilities >0.05 are clinically important. Setting: The state of Victoria, Australia. Patients: 475 EP (<28 weeks' gestation) and 570 term controls. Main outcome measures: Utilities of children born EP compared with term controls within each era, and paired differences between an EP and matched controls compared across eras. Results: Overall, 86% of survivors had utility data at 8 years of age; 475 EP and 570 controls. In all eras, parent-reported utilities were lower for children born EP compared with controls (difference in medians (95% CIs); 1991–92, −0.053 (–0.071 to –0.035); 1997, –0.053 (−0.072 to –0.034); 2005, –0.082 (−0.097 to –0.068)). Mean differences (MD) between EP children and matched controls within each era were lower in the 2005 cohort compared with both the 1991–92 cohort (MD −0.054, 95% CI −0.097 to –0.010) and the 1997 cohort (MD −0.053, 95% CI −0.097 to –0.009). Conclusion: Children born EP in the postsurfactant era have clinically important reductions in parent-reported HRQOL compared with controls, which may be worsening over time.